EKSISTENSI RIBA DALAM INVESTASI WAKAF UANG DI LUAR BANK SYARI’AH - Khoir Affandi (Asy-Syari'ah, 2019)
Abstract: According to the legal facts, the management and development of waqf money is carried out in accordance with the principles of sharia and does not conflict with the regulations of the Indonesian law. But according to the facts on the ground there is still usury in the management and development of the endowments of the money. This can be seen by the obligatory Nazir to guarantee the endowments of money managed and developed outside the shari'ah bank into shari'ah insurance. Thus, waqf money can only increase, whereas in the management and development of waqf money, Nazir can not always gain profits, there are times when Nazir loses and when Nazir experiences profit then it is done for profit between Nazir, mauquf 'alaih and Islamic financial institutions' Ah, but in the case of Nazhir's loss, the loss will be borne entirely by Nazhir. if this concept is applied in the management and development of money waqf, then what is the difference between a sharia financial institution and another bank that is not a sharia that applies the usury principle?Abstrak: Menurut fakta hukum, pengelolaan dan pengembangan wakaf uang dilakukan sesuai dengan prinsip syari’ah dan tidak bertentangan peraturan perwakafan di Indonesia. Akan tetapi menurut faktanya di lapangan masih terdapat riba dalam pengelolaan dan pengembangan wakaf uang tersebut. Hal ini terlihat dengan diwajibkannya nazhir untuk menjaminkan wakaf uang yang dikelola dan dikembangkanya di luar bank syari’ah ke dalam asuransi syari’ah. Dengan demikian, wakaf uang hanya boleh bertambah, padahal dalam pengelolaan dan pengembangan wakaf uang, tidak selamanya nazhir dapat meraih keuntungan, ada kalanya nazhir mengalami kerugian dan pada saat nazhir mengalami keuntungan maka dilakukan bagi keuntungan antara nazhir, mauquf ‘alaih dan lembaga keuangan syari’ah akan tetapi dalam kondisi nazhir mengalami kerugian maka kerugian tersebut akan ditanggung seluruhnya oleh nazhir. Apabila konsep ini yang diberlakukan dalam pengelolaan dan pengembangan wakaf uang, maka apa bedanya lembaga keuangan syari’ah dengan bank lainya yang bukan syari’ah yang menerapkan prinsip riba?